Flow driven analysis of a Darrieus water turbine - Fleisinger, Matjaž (Strojniški vestnik, 2014)
The paper discusses the development of transient sliding grid based flow driven simulation procedure for a Darrieus turbine analysis. A new computational procedure is developed within the Ansys-CFX software that allows fast solutions with good accuracy of the results. With this approach it is possible to determine the turbine power curve over its whole operating range at a given flow velocity in a single simulation. This enables comparison of several different geometry parameters to find the one that extracts the most of energy of water current. The proposed procedure allows a start-up analysis of a turbine and is also suitable to run in combination with fluid-structure interaction (FSI) analysis to analyze the mechanical behavior of the turbine blades.
Keywords: CFD simulacija; hidrokinetične turbine; model gibanja togega telesa; računalniška dinamika tekočin